INFLUENCE ANEMIA OF THE EVENT PREECLAMSIA IN MATERNAL - Eka Ameliai; Maryati Sutarno (Institute of Computer Science (IOCS), 2022)
Based on data from the Health Office of Serang Banten City, the Maternal Mortality Rate (MMR) in 2017 was 139/100,000 live births, in 2018 it increased to 158/100,000 live births. The causes of maternal death include bleeding 33% and preeclampsia/eclampsia 22%. One of the indirect causes of maternal mortality is anemia pregnancy. Anemia of pregnancy be marked with hemoglobin rate in lower 11g% resulting in placental ischemia. Placental ischemia is a one reason happening preeclampsia. Based on the foregoing, the researcher is interested in conducting a study entitled